Implementasi Fatwa DSN-MUI No. 26/DSN-MUI/III/2002 tentang Rahn Emas pada Bank Syariah - Annisa Reka Putri; Nengsih Agustin; Siti Ratna Sari (Journal of Fiqh in Contemporary Financial Transactions, 2026)
This study aims to analyze the implementation of DSN-MUI Fatwa No. 26/DSN-MUI/III/2002 in the practice of gold rahn in lslamic banks. The method used in this study is a Systematic Literature Review (SLR) with a descriptive approach. The results indicate that the implementation of DSN-MUI Fatwa No. 26 in gold pawn practices within Islamic banking is generally in accordance with Sharia principles. However, strengthening supervision and standardizing implementation are still required, along with enhancing the role of the Sharia Supervisory Board (SSB), regulatory authorities and internal understanding, to ensure that gold rahn practices truly reflect the values of justice, transparency, and benefit in line with the primary objectives of Islamic banking.